AIE‐based drug/gene delivery system: Evolution from fluorescence monitoring alone to augmented therapeutics: Special Issue: Emerging Investigators. Issue 6 (11th October 2022) - Sun, Jie; He, Xuewen
Abstract: The aggregation‐induced emission luminogens (AIEgens) with unique photophysical properties propel the rapid development of novel delivery systems for drugs and genes. In this review, we first presented numeral classic types of delivery systems based on light‐up AIEgens for real‐time monitoring of the delivery processes and evaluation of therapeutic outcomes of delivered drugs or genes. Next, general strategies were discussed for the delicately structural design of AIEgens that can self‐assemble into bright therapeutic carriers through covalent or noncovalent interactions. Furthermore, given the unprecedented enhancements in therapeutic effects through the use of multimodes of therapy, AIEgens that were endowed with multi‐properties and functionalities were investigated in the constructions of delivery systems for multimodality therapy. Especially, the combinational uses of AIE photosensitizers with chemo drug and small interference RNA (siRNA) were given as examples of augmenting the therapeutic performance in drug‐resistant treatment and moderate immunotherapy by showing synergistic effects. Abstract : The aggregation‐induced emission luminogens (AIEgens) propel the development of drug and gene delivery systems. The lit‐up AIEgens first serve for real‐time monitoring of the delivery processes and evaluation of therapeutic responses of drug/gene. The delicate design of AIEgens to form high‐level structural carrier remarkably enhances the delivery efficiency. Further, endowed with multi‐properties and functionalities, AIEgens are synergized with the delivered drug/gene for multimodality therapy.